2008
DOI: 10.1021/ja801309g
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Phase Self-Assembly of Molecular Gate Dielectrics for Thin Film Transistors

Abstract: Organic-inorganic films grown entirely via a vapor-phase deposition process and composed of highly polarizable molecular structures are investigated as gate dielectrics in organic field-effect transistors (OFETs). Molecules 1 and 2 form self-ordered thin films via hydrogen bonding, and these organic-inorganic structures exhibit large capacitances and large pentacene OFET mobilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 36 publications
1
65
0
Order By: Relevance
“…18) was demonstrated. [269] In addition, the structures of the new molecular constituents (1 and 2) are improved over the original molecular component (Stb) of SANDs by (i) their ability to self-assemble via head-to-tail intra-molecular hydrogen-bonds, and (ii) anticipated larger molecular polarizabilities than Stb. Here, the trends in dielectric permittivities are evaluated qualitatively using the Clausius-Mossotti relation e / (3 þ 2aN)/(3 À aN) (where a is the polarizability along the conjugated long axis of the molecule and N is the molecular density in cm…”
Section: à2mentioning
confidence: 99%
“…18) was demonstrated. [269] In addition, the structures of the new molecular constituents (1 and 2) are improved over the original molecular component (Stb) of SANDs by (i) their ability to self-assemble via head-to-tail intra-molecular hydrogen-bonds, and (ii) anticipated larger molecular polarizabilities than Stb. Here, the trends in dielectric permittivities are evaluated qualitatively using the Clausius-Mossotti relation e / (3 þ 2aN)/(3 À aN) (where a is the polarizability along the conjugated long axis of the molecule and N is the molecular density in cm…”
Section: à2mentioning
confidence: 99%
“…Previous work has shown that materials with large (hyper)polarizabilities generally exhibit significantly higher dielectric responses than other molecular materials. 21,39,40 In this regard, electron-donating and electron-accepting moieties are known to enhance molecular (hyper)polarizabilities when introduced in tandem to conjugated π-systems. 41−44 These molecular materials, commonly referred to as DBA materials ( Figure 1) have inspired significant research in the scientific community for implementation in nonlinear optics, 44−47 charge transfer, 48−50 and charge transport.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[ 21 ] R-SAND was prepared by depositing a ∼ 5 nm thick v-SiO x layer on the as-fabricated SAND via the post-crosslinking of a vapor-deposited HCDS fi lm. [ 28 ] For capacitance and leakage current characterization, ∼ 50 nm Au or ∼ 80 nm a-ZITO TOC top contact electrodes were deposited on the n + -Si/SAND and n + -Si/R-SAND samples by vacuum thermal evaporation at ∼ 2.0 × 10 − 6 Torr or by PLD, respectively, using shadow masks to defi ne 200 μ m × 200 μ m electrodes. For TFTs, ∼ 40 nm a-ZITO TOS fi lms were fi rst deposited, followed by Au or ZITO source/drain electrode deposition through shadow masks to produce 100 μ m × 2000 μ m channels.…”
Section: Methodsmentioning
confidence: 99%
“…[ 28 ] Figure 1b shows capacitance vs. frequency (at 2.0 V) data for SAND, R-SAND, and v-SiO x fi lms measured as n + -Si/dielectric/Au devices. Compared to SAND, which exhibits a high capacitance ( C i ) of ∼ 220 nF/cm 2 at 2.0 V/10 KHz, C i for R-SAND is ∼ 180 nF/cm 2 measured under the same conditions.…”
mentioning
confidence: 99%